Metagenomic Next-Generation Sequencing Is Highly Efficient in Diagnosing Pneumocystis Jirovecii Pneumonia in the Immunocompromised Patients - Wang, Dongsheng; Fang, Shihua; Hu, Xiaowen; Xu, Qixia; Chu, Xinmin; Mei, Xiaodong; Xie, Wang (Frontiers in Microbiology, 2022)
Purposes To explore the value of metagenomic next-generation sequencing (mNGS) in diagnosing pneumocystis jiroveciipneumonia (PJP) in the immunocompromised patients. Methods Data of 122 patients with PJP in an immunosuppressed state and 67 non-PJP patients were collected. The diagnostic efficacy of mNGS was compared with the conventional methods, including Gomori methenamine silver (GMS) staining and serum (1,3)-β-D-glucan (BDG). Changes of anti-microbial therapy for patients with PJP based on mNGS results were also reviewed. Results The diagnostic sensitivity of mNGS to PJP was higher than that of GMS and BDG (100% vs. 15 and 74.5%, p < 0.001). The diagnostic specificity (91.%) was lower than that of GMS (100%), and similar with BDG (89.6%). In addition to P. jirovecii, mNGS revealed co-pathogens like human β-herpesvirus 5, human γ-pesvirus 4, and some other opportunistic pathogens. The reads of mNGS were remarkably higher in BALF than in blood samples. Initial antimicrobial treatment was modified in 89.3% patients based on the mNGS results, and 74 cases (60.7%) were treated with anti-P. jirovecii therapy. Conclusion mNGS is highly efficient in diagnosing PJP and good at identifying pathogens in mixed infections.